Mental health and healthcare utilisation in adult asylum seekers (Swiss Medical Weekly, 2010)
We assessed a sample of unselected adult asylum seekers to determine their current mental health status and patterns of healthcare utilisation. METHOD: We included 78 unselected adult asylum seekers after their first year of residence in the Zurich area of Switzerland. The Swiss Federal Office for Migration provided their names and addresses. The current mental health of the participants was assessed through diagnostic interviews. Their use of healthcare services and the resultant costs over a 12-month period were established by reference to the records of the responsible health insurance company. RESULTS: Forty-one percent of participants had at least one psychiatric disorder, primarily major depression and posttraumatic stress disorder. Healthcare costs were about 1.8 times those of the average resident population. Asylum seekers sought medical advice more than twice as often as did average residents. While they presented high psychiatric morbidity, they received very little specific treatment. CONCLUSION: Asylum seekers incur higher healthcare costs than comparable residents. Mentally ill asylum seekers are underdiagnosed and often inadequately treated.